Preparation of Mesoporous Biochar from Cornstalk for the Chromium (VI) Elimination by Using One-Step Hydrothermal Carbonation - Chao Wang; Jun Xie; Mingdong Zheng; Jinbo Zhu; Changliang Shi (Journal of Analytical Methods in Chemistry)
Hydrothermal carbon (HTC) was prepared by the one-step hydrothermal method for Cr (VI) removal from wastewater, which was considered a “green chemistry” method. The specific surface area (SBET) of HTC was 85 m2/g with the pore size in range of 2.0–24.0 nm. FT-IR spectra analysis showed that the HTC had abundant chemical surface functional groups. The influence of adsorption parameters such as pH, HTC dosage, Cr (VI) concentration, and contact time on the removal efficiency of Cr (VI) had been investigated. When the initial concentration was 50 mg/L, pH = 6, amount of adsorbent was 0.2 g/50 ml, and adsorption time was 90 min; the Cr (VI) absorbed rate of HTC reached 98%. Batch adsorption experiments indicated that Cr (VI) adsorption data of HTC fitted the Freundlich isothermal and pseudo-second-order kinetic models. Overall, our findings provide a promising material in treatment of Cr (VI)-rich wastewater and give a clear picture of its application, which is worthy of further study.